CSR Implementation of PT Perusahaan Gas Negara, Tbk – Offtake Cimanggis Station through the Anyelir 2 Waste Bank in Harjamukti Depok City - Nur Rahmi Fajri Yanti; Respa, Chindy; Elfianto, Isa (Prospect Publishing, 2024)
To overcome the problem of waste in Cipayung landfill which has overcapacity requires cooperation from various parties. PT Perusahaan Gas Negara Tbk Offtake Cimanggis Station, which has station in the Cimanggis District of Depok City, is also involved in dealing with these problems through the Bank Sampah Anyelir 2 Program. This study aims to describe how the implementation of the PT Perusahaan Gas Negara Tbk Offtake Cimanggis Station CSR program through the Bank Sampah Anyelir 2 Program fostered partners. Qualitative method with data collection techniques using observation and documentation study of the CSR Report of PT Perusahaan Gas Negara Tbk Offtake Cimanggis Station. The implementation of CSR begins with FGD, planning, implementation, monitoring and evaluation and termination. The results of this research are that the CSR activities carried out by PT Perusahaan Gas Negara Tbk Offtake Cimanggis Station strive to continue to assist the fostered partners of Bank Sampah Anyelir 2 in each empowerment process. The processes of assistance carried out by PT Perusahaan Gas Negara Tbk Offtake Cimanggis Station are FGDs, assist the planning of the Waste Bank program, facilitate the Launching of the Bank Sampah Anyelir 2, assist waste weighing activities and conducting monitoring and evaluation every month.